Developmental dysfunction in a preclinical model of Kcnq2 developmental and epileptic encephalopathy - Miaomiao Mao; Nikola Jancovski; Yafit Kushner; Lucas Teasdale; Phan Truong; Kun Zhou; Samuel Reid; Linghan Jia; Ye Htet Aung; Melody Li; Christopher A. Reid; Sean Byars; et al. (Neurobiology of Disease)
Background: Developmental and epileptic encephalopathies (DEE) are rare but severe neurodevelopmental disorders characterised by early-onset seizures often combined with developmental delay, behavioural and cognitive deficits. Treatment for DEEs is currently limited to seizure control and provides no benefits to the patients' developmental and cognitive outcomes. Genetic variants are the most common cause of DEE with KCNQ2 being one of the most frequently identified disease-causing genes. KCNQ2 encodes a voltage-gated potassium channel KV7.2 widely expressed in the central nervous system and critically involved in the regulation of neuronal excitability. In this study, we aimed to characterise a KCNQ2 variant (K556E) found in a female patient with DEE using a heterologous expression system and a knock-in mouse model. Methods: Wild-type KCNQ2 or K556E variant were expressed in Chinese Hamster Ovary (CHO) cells (with or without KCNQ3) and their biophysical properties assessed using patch clamp recordings. We further engineered a new Kcnq2 DEE mouse model (K557E) based on the K556E variant and characterised it using behavioural, electrophysiological, and transcriptome analysis. Results: A mild loss of function was observed only when the mutant channel was co-expressed with KCNQ3 in the heterologous system. The heterozygous knock-in mice showed a reduced survival rate and increased susceptibility to induced seizures. Electrophysiology recordings in brain slices revealed a hyperexcitable phenotype for cortical layer 2/3 pyramidal neurons with retigabine (KV7 channel opener) able to rescue both the increased sensitivity to chemically-induced seizures in vivo and neuronal excitability ex vivo. Whole-brain RNA sequencing revealed numerous differentially expressed genes and biological pathways pointing at dysregulation of early developmental processes. Conclusions: Our study reports on a novel Kcnq2 DEE mouse model recapitulating aspects of the disease phenotype with the electrophysiological and transcriptome analysis providing insights into KCNQ2 DEE mechanisms that can be leveraged for future therapy development.